CLUSTER ANALYSIS IN DETERMINING SUBSOIL WATER AREAS OF SIMILAR CHEMICAL COMPOSITION IN SHYRAZ AND HORAMABAD INTERMOUNTAIN TROUGHS OF IRAN - Amjadi, Aziz; Chomko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Ground waters of Shyraz Intermountain Trough are widely used for water-supply, watering crops, in industry, and for other purposes. It is currently being planned to make extensive use of ground waters of the Horamabad Trough. Discriminating large areas of ground waters of similar chemical composition and compounds containing over 10 elements is becoming a challenging task. Chemical composition of ground waters results from a number of natural and anthropogenic processes, which affect both interchange of chemical components and the nature of their bonds. However, these bonds do not remain unaffected, and are, virtually, the outcome of a number of processes. We offer a new method that is based on the use of cluster analysis, the application of which will make it possible to discriminate ground waters of similar chemical composition in different areas. This will enable both revealing similarities and differences in the processes of water supply and discharge, which define the chemical make-up of the ground waters, threats of pollution and depletion, and taking measures on ground water preservation. The method was tested on sampling chemical composition of ground waters of Shyraz and Horamabad Intermountain Troughs in Iran. Based on the cluster analysis data of the first matrix (Shyraz Intermountain Trough) and the second matrix (Horamabad Intermountain Trough) step-by-step diagrams of merging intervals are built, and dendrograms, namely. The claster analysis data being processed, the following conclusions can be made: 1. within Shyraz Intermountain Trough, there are discriminated three areas of ground waters bearing similar chemical composition in claster 1; two areas located in claster 2; three areas in claster 3; two areas in claster 4; and one area in claster 5; 2. within Horamabad Intermountain Trough, there are discriminated two areas of ground waters bearing similar chemical composition in claster 1; three areas located in claster 2; two areas in claster 3; four areas in claster 4; and per one area in clasters 5 and 6, correspondingly; 3. changes in ground water chemical composition in Shyraz and Horamabad Intermountain Troughs are interdependent; 4. the method mentioned can be used for chemical zoning of the ground waters.